A Comprehensive Review of Pippali (Piper Longum Linn.) in Brihadtrayee. - Devda, Sapana M; Patel, Bhupesh R (International Research Journal of Ayurveda & Yoga, 2023)
Background: Piper longum linn is one of the important medicinal plant of the family piperaceae. It is highly valued from time immemorial because of its vast medicinal properties. Material & method: Detailed review with special references to various Yoga of Pippali single as well as formulations, its indication, Kalpana, Rogadhikara were compiled from Bruhadtrayi like Charak samhita, Sushruta samhita & Astang hriday. Various synonyms, its Rasa panchaka, Rogghnta were reviewed from all Nighantu available in digital format. Result: All compiled data has been presented in tabular form. The result has been mentioned with special reference to formulations, Kalpana, indications, internal or external Yoga etc. Conclusion: After reviewing all the data it is found that Pippali is widely used as single drug as well as an ingredient of various formulations. In formulations it may be used in the form of Trikatu or Panchkola or single herb as bioenhancer or to potentiate the effect of formulations and to make more penetrate and easily digestible formulations. The present article provides its detailed review from Bruhadtrai with special reference to its various formulations, Kalpana, its use as internal or external, indication etc. Findings of this review may help academicians and researchers as already reference.